Dinamika Reformasi Birokrasi di Institusi TNI: Tantangan dan Strategi Implementasi Sistem Merit dalam Tata Kelola Sumber Daya Manusia - Widianto, Anker; Muslim, Muh. Azis (Syntax Corporation, 2025)
Bureaucratic reform in military institutions is a major challenge in creating a professional, transparent, and meritocracy-based system. TNI, as a pillar of national defense, faces structural and organizational culture barriers in implementing an effective merit system. This research aims to analyze the implementation of meritocratic governance in TNI's bureaucratic reform, identify inhibiting factors, and design strategies to improve the effectiveness of the merit system. Using a qualitative approach based on literature review and policy analysis, this research found that although reforms have been carried out, resistance to change, lack of digital infrastructure, and the strong influence of seniority are the main obstacles. To overcome these challenges, data-driven reforms, digitization of HR management, and alignment of regulations with the characteristics of military organizations are needed. The results of this research are a breakthrough in building a more adaptive meritocracy model in the military environment, encouraging professionalism, and accelerating the achievement of national bureaucratic reform targets. With the right strategy, TNI can transform into a more modern and accountable institution in HR management.